Knowledge Sharing dalam Organisasi: Tinjauan Sistematis - Mulyana, Aam Rachmat; Rofaida, Rofi; Sojanah, Janah (Universitas Batanghari Jambi, 2024)
The aim of this research is to bring together the scattered literature on knowledge sharing, and analyze it to provide a better understanding. The review went through three stages: establishing the review protocol, conducting the review, and reporting the review. This research systematically reviews 110 articles in three research streams: (1) drivers of knowledge sharing (2) knowledge sharing processes, and (3) results of knowledge sharing. This research finds that organizations are advised to design knowledge sharing processes in line with their overall business goals, strategies and resources to maximize the benefits of knowledge sharing.